Vocational Students Readiness In The Face of the Industrial Revolution 4.0 and the Demands of Life in the 21st Century Skills - Edy Kurniawan; Supari Muslim; Erina Rahmadyanti; Widi Aribowo; Nita Kusumawati; Euis Ismayati; Ismet Basuki; Ruzairi Abdul rahim (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
Vocational High School (VHS) is the initial level of vocational education whose task is to prepare students to become skilled labor in the industrial field. At this time there have been many changes, related to the era of industrial revolution 4.0, and the demands of life in the 21st century. Therefore it is necessary to increase the competence of vocational students in order to respond to these changes, both related to the era of industrial revolution 4.0, and demands for skills 4C to be able to live in existence in the 21st century. How far has the implementation of Vocational Schools been able to respond to these changes and demands? To answer this question, a research is needed entitled